Atherosclerotic Cardiovascular Disease Risk Prediction in Disaggregated Asian and Hispanic Subgroups Using Electronic Health Records. Issue 14 (16th July 2019) - Rodriguez, Fatima; Chung, Sukyung; Blum, Manuel R.; Coulet, Adrien; Basu, Sanjay; Palaniappan, Latha P.
Abstract : Background: Risk assessment is the cornerstone for atherosclerotic cardiovascular disease (ASCVD) treatment decisions. The Pooled Cohort Equations (PCE) have not been validated in disaggregated Asian or Hispanic populations, who have heterogeneous cardiovascular risk and outcomes. Methods and Results: We used electronic health record data from adults aged 40 to 79 years from a community‐based, outpatient healthcare system in northern California between January 1, 2006 and December 31, 2015, without ASCVD and not on statins. We examined the calibration and discrimination of the PCE and recalibrated the equations for disaggregated race/ethnic subgroups. The cohort included 231 622 adults with a mean age of 53.1 (SD 9.7) years and 54.3% women. There were 56 130 Asian (Chinese, Asian Indian, Filipino, Japanese, Vietnamese, and other Asian) and 19 760 Hispanic (Mexican, Puerto Rican, and other Hispanic) patients. There were 2703 events (332 and 189 in Asian and Hispanic patients, respectively) during an average of 3.9 (SD 1.5) years of follow‐up. The PCE overestimated risk for NHWs, African Americans, Asians, and Hispanics by 20% to 60%. The extent of overestimation of ASCVD risk varied by disaggregated racial/ethnic subgroups, with a predicted‐to‐observed ratio of ASCVD events ranging from 1.1 for Puerto Rican patients to 1.9 for Chinese patients. The PCE had adequate discrimination, although it varied significantly by race/ethnic subgroups (C‐indices 0.66–0.83). Recalibration of the PCE did not significantly improve its performance. Conclusions: Using electronic health record data from a large, real‐world population, we found that the PCE generally overestimated ASCVD risk, with marked heterogeneity by disaggregated Asian and Hispanic subgroups.